Dramaturgi Poligami - Rinawati, Rini (FIkom Unisba, 2006)
Polygamy always creating conflicts, not only from non Islamic, but also inside Islamic people as well. Although polygamy is allowed by Islam, cultural barrier and negative perceptionsspread among people made polygamy was practiced under hidden circumstance. This phenomenon created controversies, and an analysis based on dramaturgy theoryof Goffmann would be best to examine the practice. The research found that management impression occurred both in back stage as well as in front stage. The actor is the husbandwho tried to improve his image by showing off his loyalty toward his first wife. Front stage and back stage are mixed, and in order to trace the genuine message, one must focuson nonverbal message implied in communication process among the pair(s).